2012
DOI: 10.1159/000336946
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Hypertension, Valve Calcification and Left Ventricular Hypertrophy and Geometry in Peritoneal Dialysis Patients

Abstract: Background/Aims: Cardiac valve calcification (CVC) and left ventricular (LV) abnormalities are common indicators of a poor prognosis in dialysis patients. We determined the prevalence of hypertension, CVC, LV hypertrophy (LVH) and LV geometry in peritoneal dialysis (PD) patients. Methods: Eighty-seven patients (50 female; mean age 42 ± 13 years; mean dialysis duration 46 ± 24 months) on strict salt and volume restriction, none of whom were receiving antihypertensives, were included in the study. Blood pressure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
2
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 77 publications
0
8
2
2
Order By: Relevance
“…Vascular calcification may develop in the common population [1], but may be dramatically accelerated in several clinical disorders, particularly chronic kidney disease (CKD) [2,3,4,5,6,7,8,9,10,11,12,13,14]. Recent observations shed new light on the role of mineralocorticoids in triggering of vascular calcification [6].…”
Section: Introductionmentioning
confidence: 99%
“…Vascular calcification may develop in the common population [1], but may be dramatically accelerated in several clinical disorders, particularly chronic kidney disease (CKD) [2,3,4,5,6,7,8,9,10,11,12,13,14]. Recent observations shed new light on the role of mineralocorticoids in triggering of vascular calcification [6].…”
Section: Introductionmentioning
confidence: 99%
“…The similar or even higher rates of valve calcification have been reported in several studies in prevalent HD and PD patients. 18,19 However, the reduction recorded valvular calcification is only based on regression in mitral valves calcification. The number of patients with aortic calcifications at the end of the study is even slightly higher.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Aronow reported that among people aged over 62 years, those with diabetes were more likely to develop cardiac valve calcification [25]. In another study, peritoneal dialysis patients with cardiac valve calcification had higher systolic blood pressure [26]. In this study, nonetheless, we only found that the course of hypertension was longer and hypertension duration-stage product was higher in the AVC-positive group compared to the AVC-negative group, although multivariate regression analysis revealed no significant difference in these two parameters.…”
Section: Discussionmentioning
confidence: 99%